Pengaruh penggunaan pankreas kambing awetan terhadap kekuatan tarik dan kemuluran kulit kras kambing - Lutfi, Muchtar (Majalah Kulit, Karet, dan Plastik, 1991)
Took 10 pieces salted goat skins which same quality, cut in 20 sides follow the back bone line devided into 5 groups, each group consist 4 sides. All this sample be processed to crust leather accorfing to IRDLAI procedure. In tbating processing the substitute for oropon was cured of goat pancreas.For 5 groups sample each used 0; 0,75 ;1,5 ; 2,25 and 3 procentage of cured pancreas. For tensile strength and stretch testing used the part of croupon, shoulder and belly. Analisis static using CRD nested sample and factorial 3 Ã 5 and subsequently be done Tukey test. There was a real differences (P<0,01) betweem temsile strength by effects of concentration of pancreas also with itâs stretch.The best consentration can be suggested were 0,75 ; 1,5 ; 2,25 procentage. Average tensile strength for each of them were 183,2 Kg/cm2 ; 177,3 Kg/cm2 and 207,1 Kg/cm2, and the stretch wich close with the standart only on the concentration 2,25% that was 66,6%.